SREADING AND FORMS OF DOG DEMODICOSIS COURSE IN THE CITY OF ODESA - Bogach, M. V.; Yuskiv, I. D.; Bogach, E. M.; Starkiv, V. D. (Scientific Progress & Innovations, 2020)
Dog demodicosis is a chronic disease characterized by inflammation and desquamation of the skin horny layer, a decrease in the body immune status, and expressed emaciation of the animal. Demodex spp. is considered pathogenic when its amount increases and affects the dermis. Dog demodicosis is a disease, which occurs as a result of rapid propagation and release of demodectic ticks, which leads to local or generalized skin inflammation and is accompanied by hair loss, papules, pustules, strumas and folds of the skin, resulting in emaciation and sometimes death of animals. The spreading of the invasion is accompanied by deterioration in the general condition of the infected dogs and the disease clinical picture. Therefore, the study of the clinical manifestation of demodicosis, as one of the indicators of a comprehensive diagnostics of this disease, is relevant. Three species of sarcoptiform and thrombidiform ticks, causative agents of carnivores’ acaroses, have been registered in Odesa: Demodex canis, Otodectes cynotis, and Sarcoptes canis. In the general acarine dog pathology in the city of Odessa, the mass fraction of demodicosis is 55.6 %, otodectosis – 25.4 % and sarcoptic mange – 19.0 %. The susceptibility of dogs to demodicosis causative agent depends on the age and sex of the animals. Most often, dogs at the age of 6 months to 1 year (25.8 %), as well as dogs 1- 2 years old (22.7 %) are infected. Females were found to be more sensitive to the pathogen and accounted for 57.4 %. The most affected by the local form of demodicosis were dogs under the age of 6 months (89.9 %), and generalized form – over 10 years old (72.4 %). Demodectic mange was most pronounced in autumn (34.5 %) and spring (29.1 %), somewhat less in summer (23.9 %) and winter (12.5 %).